Pocketguide CT protocols / Ahmad Syakir Muhamad ... [et al.] - Muhamad, Ahmad Syakir; Salleh, Jomar; Chawfa, Fazeamin; Anuar, Muhammad Asyraf (2019)
Pocket guide CT protocol is an application that is build for the phones that can grant access on insights and new knowledge on how to perform CT scan procedures. So what is a CT scan? What does it have to do with protocol? To make it easier to understand, imagine a junior chef during a busy dinner service, he is slammed with many orders, would not it be nice if there is an app that can help the chef through the recipes. So that is what pocketguide CT protocol application is all about. It aids the CT technologist or operator to execute CT procedure accordingly. It provides step by step guide on how to get the best result out of a CT examination. This application does not intent to replace the CT workstation but to act as a supplementary instruction and insights for the CT technologist on how to achieve the best result from the CT examination. The target market for this innovation is mainly for radiographers that is qualified in CT scan service. Students can be benefited through this application by learning and relating the techniques and protocol during their clinical postings. Physician also can be benefited from this application by understanding the idea of what the patient is going through in a CT examination. To describe on how the idea of this application is basically from a single word, "accessibility". Users will have a guide on the palm of their hand, fast and without ambiguity towards the inputs this application provides.